Medical Crossword Puzzles: An Effective Formative Assessment Tool to Promote Learning - M. B. , Sannathimmappa (Advanced Concepts in Medicine and Medical Research Vol. 5, 2023)
This chapter aimed to describe the students ‘perceived benefits from Crossword puzzle-based learning. Using active-learning strategies in the classroom makes learning more engaging and gives students more motivation. Given that they spark curiosity, encourage critical thinking, improve comprehension of concepts, and serve to reinforce lecture content, crossword puzzles are thought to be an engaging instructional tool for formative assessment. The study used free online resources, crossword puzzles for the students during microbiology and immunology lectures. These lectures are part of the Microbiology and Immunology integrated course taught in the MD3 year curriculum of the College of Medicine and Health Sciences. National University of Science and Technology, Oman. Students’ perceptions of the crossword puzzle activity were assessed through an 8-item questionnaire using a 5-point Likert scale. The data was collected, tabulated, and statistically analyzed. Most of the students (89.4%%) suggested for more frequent use of crossword puzzles in the classroom as it is great fun doing in the classroom and unique way of testing their comprehension of the lecture contents. Nearly 86% of the students indicated that crossword puzzles helped them to improve their examination grades. Students perceived that crossword puzzles enhanced their learning of microbiology and immunology. Crossword puzzles in the classroom are an easy, imaginative, and useful way to add active learning to many medical courses, such as Immunology and Microbiology.